Effects of O addition on the thermal behaviour of hard W-N sputtered coatings - Louro, C. (2009)
The structural thermal behaviour of three W-O-N sputtered coatings with similar metalloid to metal ratio (~2.1) was investigated up to 900 °C after annealing in a vacuum tube furnace as well as in-situ HT-XRD under a controlled atmosphere of Ar-5%H2. The as-deposited microstructure of the coatings consisting in a nanocomposite of low-order W-O and W-N phases evaluated differently as a function of the oxygen content. The W-O-N film containing more than 27 at.% O delaminated severely from the steel substrates for temperatures as low as 500 °C. In opposite, for the coatings with less O content, the low range order of the as-deposited structure was maintained up to 800 °C and with further annealing crystallized into a mixture of WO2 and W2N. The thermal behaviour of the oxynitride films overcame that observed for oxygen-free nitride ones. This is due to the greater N content retaining during annealing treatment, in opposite to the W-N films which give rise to the single metallic [alpha]-W phase. The structural and compositional evolution supported the hardness behaviour obtained by the thermal treatment in protective ambiance